2011
DOI: 10.1038/bjc.2011.7
|View full text |Cite
|
Sign up to set email alerts
|

A multi-centre randomised phase III trial of Dexamethasone vs Dexamethasone and diethylstilbestrol in castration-resistant prostate cancer: immediate vs deferred Diethylstilbestrol

Abstract: Background:The role of further hormone therapy in castration-resistant prostate cancer (CRPC) remains unclear. We performed a multi-centre randomised phase III study comparing the use of Dexamethasone, Aspirin, and immediate addition of Diethylstilbestrol (DAiS) vs Dexamethasone, Aspirin, and deferred (until disease progression) addition of Diethylstilbestrol (DAdS).Methods:From 2001 to 2008, 270 men with chemotherapy-naive CRPC were randomly assigned, in a 1 : 1 ratio, to receive either DAiS or DAdS. They wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…Phase 2 studies of low-dose, daily dexamethasone have reported somewhat higher PSA response rates of 50-60%, with median time to PSA progression from 7 mo to 8 mo [4,11]. The two largest studies, including a combined total of 237 patients treated with dexamethasone as a single agent, both reported PSA response rates of around 50% [4,12]. The published activity data for low-dose, daily dexamethasone in CRPC are summarised in Table 1.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Phase 2 studies of low-dose, daily dexamethasone have reported somewhat higher PSA response rates of 50-60%, with median time to PSA progression from 7 mo to 8 mo [4,11]. The two largest studies, including a combined total of 237 patients treated with dexamethasone as a single agent, both reported PSA response rates of around 50% [4,12]. The published activity data for low-dose, daily dexamethasone in CRPC are summarised in Table 1.…”
Section: Introductionmentioning
confidence: 94%
“…In these trials, the PSA response rate to prednisolone has ranged from 16% to 24%, and the median time to PSA progression has ranged from 2 mo to 6 mo [6][7][8][9][10]. The published activity data for prednisolone in CRPC are summarised in Table 1 [3,4,[6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Men were randomised to receive dexamethasone and aspirin with either the immediate or deferred (at progression) addition of DES. 5 The results of the study showed that there were no significant advantages in using both drugs in combination as initial therapy in terms of PSA response rate, progression-free survival (8.1 months in both arms), overall survival or quality of life. In view of the fact that the potential toxicity of DES is higher than that of dexamethasone, the authors have concluded that a preferred strategy could be to defer DES until failure of dexamethasone when using these agents in CRPC.…”
Section: The Evidencementioning
confidence: 86%
“…Second-line endocrine treatment was mainly LHRH agonist in the iAAm group followed by Stilboestrol plus or minus Dexamethasone [14][15][16] followed by chemotherapy with CL56, a 2-week treatment with oral Chlorambucil and Lomustine repeated 8 weekly [17]. This had been shown to produce equivalent survival to Docetaxel with the added advantage that when given without continued androgen suppression, patients often responded a second time to previous endocrine treatments that they had initially failed and were considered to have progressed to hormone-refractory disease [17][18][19].…”
Section: Methodsmentioning
confidence: 99%